Cawson's essentials of oral pathology and oral medicine - Cawson, R. A; Odell, E. W (Edinburgh ; New York : Churchill Livingstone, 2008)
"The book commences with a practical discussion of the role of history and examination followed by a detailed explanation of the investigations commonly used in clinical practice. The volume then provides a step-by-step guide to the diagnosis and management of a series of conditions ranging from disorders of tooth development, caries, pulpitis, periodontisis and other infections, to pigmented lesions, salivary gland disease and oral cancer. Systemic diseases such as leukaemias, HIV, and allergy are also discussed in relation to oral healthcare as well as topics of special interest such as the management of pain and anxiety, complications of systemic drug treatment and medical emergencies." "The new edition of this classic text is ideal for senior dental students and qualified practitioners taking post-graduate exams." --Book Jacket
Includes bibliographical references and index
Keywords: Mouth -- Diseases; Oral manifestations of general diseases; Mouth -- Surgery; Dentistry; Surgery, Oral; Dentistry, Operative; Mouth Diseases; Tooth Diseases